2017
DOI: 10.4174/astr.2017.92.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Complete mesocolic excision in right hemicolectomy: comparison between hand-assisted laparoscopic and open approaches

Abstract: PurposeTo demonstrate the feasibility, safety, and technical strategies of hand-assisted laparoscopic complete mesocolic excision (HAL-CME) and to compare oncological outcomes between HAL-CME and the open approach (O-CME) for right colon cancers.MethodsPatients who were scheduled to undergo a right hemicolectomy were divided into HAL-CME and O-CME groups. Measured outcomes included demographic variables, perioperative parameters, and follow-up data. Demographic variables included age, sex distribution, body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 30 publications
10
29
1
1
Order By: Relevance
“…These results were in agreement with those reported by Sheng et al, 2017 who stated that, the open and laparoscopic techniques were the same in age, sex distribution, tumor localization, and potential comorbidities (all p>0.05) 11 . However, Vendramini et al, 2012 observed that, there was a statistical significant difference (p=0.049) with a higher prevalence of open procedure between the patients aged 60 or over 12 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in agreement with those reported by Sheng et al, 2017 who stated that, the open and laparoscopic techniques were the same in age, sex distribution, tumor localization, and potential comorbidities (all p>0.05) 11 . However, Vendramini et al, 2012 observed that, there was a statistical significant difference (p=0.049) with a higher prevalence of open procedure between the patients aged 60 or over 12 .…”
Section: Discussionsupporting
confidence: 93%
“…These results were close to the study of Sheng et al, 2017 who demonstrated that, the median follow up duration of the laparoscopic and open groups was 20.1±4.6 months. 11…”
Section: Discussionmentioning
confidence: 99%
“…With experience gained, general complication rate in our centre is also decreasing [1,4,14]. While our length of stay data compare favourably with other reports [1,6,24].…”
Section: Discussionsupporting
confidence: 77%
“…With experience gained, general complication rate in our centre is also decreasing [1,4,14]. While our length of stay data compare favourably with other reports [1,6,24]. There is still arguments against HALS, mainly because of incision length [5,17] or uncertainty about long-term results such as development of adhesive small bowel obstruction or ventral hernias В недавних исследованиях было подчёркнуто влияние количества лимфатических узлов в препарате на онкологические результаты.…”
Section: Discussionsupporting
confidence: 62%
“…По мере набора опыта снизилась общая частота осложнений в нашем центре [1,4,14]. Следует отметить, что в нашем исследовании длительность послеоперационного пребывания пациента в стационаре выгодно отличалась от результатов, опубликованных в других работах [1,6,24]. До сих пор существуют доводы против HALS, главным образом, из-за длины кожного разреза [5,17] или неопределенности в отношении отдалённых результатов, таких как развитие острой спаечной кишечной непроходимости и послеоперационной вентральной грыжи [25].…”
Section: Discussionunclassified